Electro-biocatalytic treatment of petroleum refinery wastewater using microbial fuel cell (MFC) in continuous mode operation. (December 2016) - Srikanth, Sandipam; Kumar, Manoj; Singh, Dheer; Singh, M.P.; Das, B.P.
Graphical abstract: Highlights: Contaminants present in refinery wastewater treated in continuous mode MFC operation. Continuous mode operation showed higher performance (225 ± 1.4 mW/m 2 ) over batch mode. GC chromatogram showed significant removal of hydrocarbon content of C6 to C40. Phenol and sulfide removal was also significant in continuous mode operation. Projected power yields showed the possibility of process up-scaling. Abstract: Refinery wastewater (RW) treatment in microbial fuel cell (MFC) was studied in batch mode operation followed by continuous mode operation with 8 h and 16 h hydraulic retention time (HRT). The MFC performance was evaluated in terms of power density, organics removal, specific contaminants (oil & grease, phenol and sulfide) removal and energy conversion efficiency with respect to operation mode. Higher power density of 225 ± 1.4 mW/m 2 was observed during continuous mode operation with 16 h HRT along with a substrate degradation of 84.4 ± 0.8% including the 95 ± 0.6 of oil content. The columbic efficiency during this operation was about 2 ± 0.8% and the projected power yield was 340 ± 20 kW h/kg CODR /day. Batch mode operation also showed good substrate degradation (81 ± 1.8%) but took longer HRT which resulted in significantly low substrate degradation rate (0.036 ± 0.002 kg CODR /m 3 -day) over continuous mode operation (1.05 ± 0.01 kg CODR /m 3 -day). Overall, current study depicted the possibility of utilizing RW as substrate in MFC for power generation along with its treatment.